PENGARUH PEMIKIRAN ULAMA SUMATERA SELATAN ABAD XX TERHADAP DINAMIKA DAN PRODUKTIVITAS MASYARAKAT SUMATERA SELATAN - Nurseri Hasnah Nasution (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2018)
In the twentieth century, South Sumatra was characterized by the postmodernist religious phenomenon and the problems diverse religious articulation. To respond to these phenomena and problems, some South Sumatra Islamic scholars such as K.H. Anwar Kumpul, K.H. M. Zen Syukri, K.H. Zainal Abidin Fikry formulated theocentric theological thought. Their theological thought and pattern influenced the progress of civilization in South Sumatra. Subject matter of theocentric theological thought K.H. Anwar Kumpul, K.H. M. Zen Syukri, K.H. Zainal Abidin Fikry consists of: the position of reason, the function of revelation, the concept of faith, human actions, anthropomorphism, beatific vision, the attributes of God, the deeds of God, the power of God, the justice and the word of God. Thought and style of Islamic Theology such as K.H. Anwar Kumpul, K.H. M. Zen Syukri, K.H. Zainal Abidin Fikry is relevant for the condition of postmodern society, people experiencing psychosocial stressors, Malay society, sociological and theological societies, and trichotomization of South XX-XXI century society. This study deconstructs the collective perceptions and memories introduced by Harun Nasution. He conjures that traditional theology is the cause of stagnation.